Gerakan Dakwah Ustadz Khalid Basalamah di Platform Youtube : Analisis Strukturasi Anthony Giddens - M. Syahrul Ulum; Mega Dwi Agustin; Mey Safitri (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2025)
This research aims to analyze social practices in Ustadz Khalid Basalamah's da'wah movement on the YouTube platform using Anthony Giddens' Social Practice Theory approach. The research method used is qualitative with a library study focus, which involves collecting data from various sources such as journals, books, articles, YouTube and related literature. This research explains social practices in the context of Ustadz Khalid Basalamah's da'wah movement on YouTube, identifying findings that are relevant to Anthony Giddens' Social Practice Theory. A qualitative approach was used to explore the data and understand how the practices of the da'wah movement were reflected in Giddens' theoretical perspective. The results of data analysis will be linked to the concept of Anthony Giddens' Social Practice Theory, so that it can provide a deep understanding of the phenomenon of Ustadz Khalid Basalamah's preaching movement on YouTube. It is hoped that this research can contribute to the theoretical understanding of social practices and the phenomenon of da'wah in the digital era, by connecting empirical findings with the conceptual framework provided by Anthony Giddens.